Lignin sulfonate / gelatin composite hydrogel electrolyte, preparation method and aqueous zinc ion battery
By using sulfonated lignin/gelatin composite hydrogel electrolyte in aqueous zinc ion batteries, the problems of zinc dendrites growth and electrode/electrolyte interface side reactions are solved, significantly improving the rate performance and cycling performance of the battery, and improving the safety and reliability of the battery.
Patent Information
- Application Number
- CN202411717527.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
AI Technical Summary
During the charge and discharge cycle, aqueous zinc ion batteries are prone to zinc dendrites growth and electrode/electrolyte interface side reactions, resulting in poor rate performance and circulation performance, and are prone to short circuits inside the battery and leakage of electrolyte, affecting the safety and reliability of the battery.
The sulfonated lignin/gelatin composite hydrogel electrolyte is used to prepare a sulfonated lignin composite gelatin hydrogel hydrogel by mixing the sulfonated lignin with gelatin and adding zinc-manganese salt solution, and uniformly preparing it with the aqueous electrolyte to form a composite hydrogel electrolyte.
This electrolyte can effectively inhibit the formation and growth of zinc dendrites, reduce the corrosion of zinc negative electrodes, significantly improve the rate performance and circulation performance of aqueous zinc ion batteries, extend the service life of the battery, and improve the safety and reliability of the battery.
Smart Images

Figure CN119601792A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to a sulfonated lignin / gelatin composite hydrogel electrolyte and a preparation method thereof, and an aqueous zinc ion battery. Background Art
[0002] Aqueous zinc-ion batteries have the advantages of high theoretical specific capacity, high coulombic efficiency, high energy density, safety and environmental protection, and are considered to be one of the next-generation candidate batteries with the most promising commercial application prospects. However, the practical application of zinc-ion batteries is severely restricted by defects such as zinc dendrite growth and electrode / electrolyte interface side reactions during the charge and discharge cycle, which greatly affects its rate performance and cycle performance. At the same time, the presence of dendrites may pierce the diaphragm, causing internal short circuits in the battery, further hindering the commercialization of aqueous zinc-ion batteries. Therefore, in recent years, people have carried out a lot of research on inhibiting the growth of zinc dendrites, mainly including the structural design and surface modification of negative electrode materials (such as constructing a coating with a nanopore structure, polymer layer coating modification, etc.), electrolyte component optimization, and the development of electrolyte additives. Although these methods can inhibit the formation and growth of zinc dendrites to a certain extent, they have limited effect on alleviating the side reactions of metallic zinc in an aqueous environment due to its inherent activity. Another key problem of aqueous zinc-ion batteries is that after suffering severe physical damage, electrolyte leakage may occur, resulting in deterioration of the battery's energy storage function, poor reliability and maintainability, and even major safety accidents. Compared with aqueous electrolytes, gelatin hydrogel electrolytes can improve the discharge capacity of zinc-ion batteries, but at the same time reduce their cycle stability, causing the capacity of zinc-ion batteries to decay too quickly during the charge and discharge process and a decrease in coulombic efficiency. This is because although the gel electrolyte composed of pure gelatin can store electrolyte, it has no ability to regulate the zinc deposition process at the zinc negative electrode interface, resulting in a "tip effect" that causes uneven zinc deposition and zinc dendrites that pierce the gel electrolyte, causing the positive and negative electrodes of the battery to short-circuit and damage the battery, affecting the battery life. Summary of the invention
[0003] The first object of the present invention is to provide a sulfonated lignin / gelatin composite hydrogel electrolyte to solve the technical problems of corrosion of the zinc negative electrode and the formation and growth of zinc dendrites by the pure gelatin hydrogel electrolyte.
[0004] The second object of the present invention is to provide a method for preparing a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0005] The third object of the present invention is to provide an aqueous zinc ion battery.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0007] A sulfonated lignin / gelatin composite hydrogel electrolyte comprises a sulfonated lignin composite gelatin hydrogel and an aqueous electrolyte. The sulfonated lignin composite gelatin hydrogel is prepared by uniformly mixing gelatin, water, a zinc-manganese salt solution and sulfonated lignin.
[0008] Furthermore, the mass ratio of the sulfonated lignin to gelatin is 1:3 to 1:200; the mass ratio of gelatin to water is 1:2 to 1:10; the mass ratio of gelatin to zinc-manganese salt solution is 1:2 to 1:10; and the pH of the water is 2 to 6.
[0009] The mass ratio of the sulfonated lignin to gelatin is preferably 1:10 to 1:100; the mass ratio of gelatin to water is preferably 1:3 to 1:6; the mass ratio of gelatin to zinc-manganese salt solution is preferably 1:4 to 1:8; and the pH of the water is preferably 4 to 5.
[0010] Furthermore, the sulfonated lignin includes lignin sulfonate, a byproduct of the sulfite pulping process, or one or more modified products of alkali lignin, enzymatic lignin, organic solvent lignin, steam explosion lignin prepared by graft sulfonation, sulfomethylation, and sulfite sulfonation.
[0011] The sulfonated lignin is preferably one or more of alkali lignin, enzymatically hydrolyzed lignin, and modified products prepared by grafting sulfonation and sulfomethylation.
[0012] Furthermore, the zinc-manganese salt solution includes zinc salt and manganese salt, the zinc salt includes one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc bromide, zinc acetate, and zinc trifluoromethanesulfonate; the manganese salt includes one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate, and manganese trifluoromethanesulfonate; the final concentration of the zinc salt in the zinc-manganese salt solution is 0.3-1.5 mol / L, and the final concentration of the manganese salt is 0.01-0.2 mol / L.
[0013] The zinc salt is preferably zinc sulfate, zinc nitrate, zinc chloride and zinc bromide, and the manganese salt is preferably manganese sulfate, manganese nitrate, manganese chloride and manganese bromide; the final concentration of the zinc salt in the zinc-manganese salt solution is preferably 1-1.5 mol / L, and the final concentration of the manganese salt is preferably 0.1-0.15 mol / L.
[0014] Further, the mass ratio of the sulfonated lignin composite gelatin hydrogel to the aqueous electrolyte is 1:2 to 1:5; the aqueous electrolyte is prepared by dissolving and mixing water-soluble zinc salts and water-soluble manganese salts, wherein the water-soluble zinc salts include one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc bromide, zinc acetate, and zinc trifluoromethanesulfonate; the water-soluble manganese salts include one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate, and manganese trifluoromethanesulfonate; the final concentration of the water-soluble zinc salt in the aqueous electrolyte is 1.5 to 3 mol / L, and the final concentration of the water-soluble manganese salt is 0.1 to 0.4 mol / L. The pH of the aqueous electrolyte is 3.5 to 7.
[0015] The mass ratio of the sulfonated lignin composite gelatin hydrogel to the aqueous electrolyte is preferably 1:3 to 1:5; the water-soluble zinc salt is preferably zinc sulfate, zinc nitrate, zinc chloride, zinc bromide, and the water-soluble manganese salt is preferably manganese sulfate, manganese nitrate, manganese chloride, and manganese bromide; the final concentration of the water-soluble zinc salt in the aqueous electrolyte is preferably 2 to 3 mol / L, and the final concentration of the water-soluble manganese salt is preferably 0.2 to 0.4 mol / L. The pH of the aqueous electrolyte is preferably 4 to 5.
[0016] A method for preparing a sulfonated lignin / gelatin composite hydrogel electrolyte comprises the following steps: 1) adding gelatin and sulfonated lignin into water, heating and stirring to form a gelatin / sulfonated lignin aqueous solution, adding a zinc manganese salt solution into the gelatin / sulfonated lignin aqueous solution, stirring to obtain a mixed solution, and allowing the mixed solution to stand at low temperature to obtain a sulfonated lignin composite gelatin hydrogel; and 2) immersing the sulfonated lignin composite gelatin hydrogel in an aqueous electrolyte to obtain the electrolyte.
[0017] Furthermore, in step 1), the heating temperature is 60-80°C; and the low temperature is 0-10°C.
[0018] The heating temperature is preferably 65 to 75°C, and the low temperature is preferably 2 to 6°C.
[0019] Furthermore, the soaking time in step 2) is 2 to 6 days.
[0020] The soaking time is preferably 3 to 4 days.
[0021] An aqueous zinc ion battery comprises the above-mentioned sulfonated lignin / gelatin composite hydrogel electrolyte.
[0022] Beneficial effects of the present invention:
[0023] The mechanism of the present invention is:
[0024] The present invention applies sulfonated lignin / gelatin composite hydrogel electrolyte to aqueous zinc ion batteries, which can effectively inhibit the formation and growth of zinc dendrites, reduce byproducts at the interface between the gel electrolyte and the zinc negative electrode, and slow down the corrosion of the gel electrolyte to the zinc negative electrode, thereby significantly improving the rate performance and cycle performance of the aqueous zinc ion battery. This is mainly because the sulfonate functional groups in the sulfonated lignin can react with the zinc ions in the gel electrolyte to generate positive and negative charges, regulate the uniform deposition and stripping of zinc ions on the surface of the zinc negative electrode, and effectively inhibit the formation of zinc dendrites. At the same time, lignin has functional groups such as hydroxyl and carboxyl groups, which buffer the excess H at the interface between the zinc negative electrode and the gel electrolyte. + / OH - , thereby preventing the drastic pH change at the interface between the zinc negative electrode and the gel electrolyte, maintaining the stability of the interface environment between the zinc negative electrode and the gel electrolyte, further reducing the generation / accumulation of by-products, and slowing down the corrosion of the zinc negative electrode by the gel electrolyte. In addition, the functional groups on the lignin are also fixed on the gel network structure, and only play a regulatory role at the interface between the zinc negative electrode and the gel electrolyte, and will not be adsorbed on the zinc negative electrode to affect the deposition and stripping of zinc ions. Therefore, the sulfonated lignin / gelatin composite hydrogel electrolyte can not only effectively prevent the formation of zinc dendrites, but also reduce the corrosion of the zinc negative electrode. Based on this, the gel electrolyte provided by the present invention can significantly improve the rate performance and cycle performance of aqueous zinc ion batteries.
[0025] The advantages of the present invention are mainly reflected in the following aspects:
[0026] The present invention provides a sulfonated lignin / gelatin composite hydrogel electrolyte, which can effectively inhibit the formation and growth of zinc dendrites, alleviate the corrosion of zinc negative electrode, thereby reducing the specific capacity loss of aqueous zinc ion batteries, and significantly improving their rate performance and cycle performance. The sulfonated lignin used in the present invention is simple to prepare, and can directly use the sulfonated lignin in the purified papermaking waste liquid to utilize waste resources; it can also be prepared by directly heating and stirring sulfonates and lignin to react. Sulfonates and lignin are both cheap raw materials, and the process of preparing sulfonated lignin is also simple and environmentally friendly, without using toxic reagents. The sulfonated lignin / gelatin composite hydrogel electrolyte of the present invention has good stability, strong water retention, low cost and wide sources, which helps to promote the industrial production and popularization and application of safe, environmentally friendly, low-cost and excellent-performance aqueous zinc ion batteries, and has great application prospects in future flexible zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte in Example 1 and the reference gel electrolyte are shown in Figure 1, where a is a rate performance diagram and b is a cycle performance diagram;
[0028] Figure 2 The performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte in Example 2 and the reference gel electrolyte are shown in Figure 2, where a is a rate performance diagram and b is a cycle performance diagram;
[0029] Figure 3 The performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte in Example 3 and the reference gel electrolyte are shown in Figure 3, where a is a rate performance diagram and b is a cycle performance diagram;
[0030] Figure 4 The performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte in Example 4 and the reference gel electrolyte are shown in Figure 4, where a is a rate performance diagram and b is a cycle performance diagram;
[0031] Figure 5 The performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte and the reference gel electrolyte in Comparative Example 1 are shown in Figure 1, where a is a rate performance diagram and b is a cycle performance diagram;
[0032] Figure 6 These are performance test results of aqueous zinc ion batteries using the sulfonated lignin / gelatin composite hydrogel electrolyte in Comparative Example 2 and the reference gel electrolyte, where a is the rate performance diagram and b is the cycle performance diagram. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments of the present invention and the accompanying drawings.
[0034] Figure 1-6 The test gel electrolytes correspond to the sulfonated lignin / gelatin composite hydrogel electrolytes prepared in Examples 1-4 and Comparative Examples 1-2, respectively.
[0035] The aqueous zinc ion battery includes a battery shell, a core and a gel electrolyte, which are sealed in the battery shell. The core includes a positive electrode sheet that can react with zinc ions, a zinc negative electrode and a sulfonated lignin / gelatin composite hydrogel electrolyte located between the positive and negative electrodes.
[0036] Example 1
[0037] In Example 1, the zinc-manganese salt solution includes zinc sulfate with a final concentration of 1.5 mol / L and manganese sulfate with a final concentration of 0.15 mol / L. The aqueous electrolyte includes zinc sulfate with a final concentration of 3 mol / L and manganese sulfate with a final concentration of 0.4 mol / L, and the pH of the aqueous electrolyte is 4. The pH of water is adjusted to 4 by sulfuric acid. Sulfonated alkali lignin is prepared by grafting sulfonation of alkali lignin and sulfonate.
[0038] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Example 1
[0039] Add 2g of gelatin and 0.2g of sulfonated alkali lignin to 10g of water, heat and stir at 70°C for 1 hour until the gelatin and sulfonated alkali lignin are completely dissolved to obtain a gelatin / sulfonated lignin aqueous solution, then add 10g of zinc manganese salt solution, heat and stir at 70°C for 0.5 hour to mix evenly to obtain a mixed solution, let the mixed solution stand at 4°C for 8 hours to obtain a sulfonated lignin composite gelatin hydrogel, soak the sulfonated lignin composite gelatin hydrogel in 70g of aqueous electrolyte for 72 hours to obtain a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0040] The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and the positive electrode sheet and the zinc negative electrode are assembled into a battery shell to obtain an aqueous zinc ion battery.
[0041] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0042] 2g of gelatin was added to 10g of water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then 10g of zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain reference gel electrolyte. The assembly process of aqueous zinc ion battery using reference gel electrolyte is the same as above.
[0043] 3. Electrochemical performance test:
[0044] The aqueous zinc ion batteries using the gel electrolyte of Example 1 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0045] 4. Results Analysis
[0046] Depend on Figure 1 (a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 1 is significantly higher than the specific capacity of the aqueous zinc ion battery using the reference gel electrolyte; Figure 1(b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the specific discharge capacity of the aqueous zinc ion battery using the gel electrolyte of Example 1 is higher than that of the aqueous zinc ion battery using the reference gel electrolyte. This shows that the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Example 1 is significantly reduced compared to the specific capacity loss of the aqueous zinc ion battery using the reference gel electrolyte. This is mainly because compared with the reference gel electrolyte, the gel electrolyte of Example 1 has a stronger ability to inhibit the formation and growth of zinc dendrites, and reduces the side reaction between the gel electrolyte and the zinc negative electrode, thereby effectively slowing down the corrosion of the gel electrolyte to the zinc negative electrode, thereby reducing the specific capacity loss of the aqueous zinc ion battery, and significantly improving the rate performance and cycle performance of the aqueous zinc ion battery.
[0047] Example 2
[0048] The zinc-manganese salt solution of Example 2 includes zinc nitrate with a final concentration of 1.5 mol / L and manganese nitrate with a final concentration of 0.15 mol / L. The aqueous electrolyte includes zinc nitrate with a final concentration of 3 mol / L and manganese nitrate with a final concentration of 0.4 mol / L, and the pH of the aqueous electrolyte is 4. The pH of water is adjusted to 4 by sulfuric acid. Sulfonated alkali lignin is prepared by a sulfonation modification method of alkali lignin grafted with sulfonate.
[0049] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Example 2
[0050] Add 2g of gelatin and 0.2g of sulfonated alkali lignin to 10g of water, heat and stir at 70°C for 1 hour until the gelatin and sulfonated alkali lignin are completely dissolved to obtain a gelatin / sulfonated lignin aqueous solution, then add 10g of zinc manganese salt solution, heat and stir at 70°C for 0.5 hour to mix evenly to obtain a mixed solution, and then let it stand at 4°C for 8 hours to obtain a sulfonated lignin composite gelatin hydrogel, soak the sulfonated lignin composite gelatin hydrogel in 70g of aqueous electrolyte for 72 hours to obtain a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0051] The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and the positive electrode sheet and the zinc negative electrode are assembled into a battery shell to obtain an aqueous zinc ion battery.
[0052] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0053] 2g of gelatin was added to 10g of water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then 10g of zinc manganese salt solution was added, heated and stirred at 70°C for 1 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain a reference gel electrolyte. The assembly process of the aqueous zinc ion battery using the reference gel electrolyte is the same as above.
[0054] 3. Electrochemical performance test
[0055] The aqueous zinc ion batteries using the gel electrolyte of Example 2 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0056] 4. Results Analysis
[0057] Depend on Figure 2 (a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 2 is significantly higher than the specific capacity of the aqueous zinc ion battery using the reference gel electrolyte; Figure 2 (b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the discharge specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 2 is higher than that of the aqueous zinc ion battery using the reference gel electrolyte, which indicates that the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Example 2 is significantly reduced compared to the specific capacity loss of the aqueous zinc ion battery using the reference gel electrolyte. This is mainly because compared with the reference gel electrolyte, the gel electrolyte of Example 2 has a stronger ability to inhibit the formation and growth of zinc dendrites, and reduces the side reaction between the gel electrolyte and the zinc negative electrode, thereby effectively slowing down the corrosion of the gel electrolyte to the zinc negative electrode, thereby reducing the specific capacity loss of the aqueous zinc ion battery, and significantly improving the rate performance and cycle performance of the aqueous zinc ion battery.
[0058] Example 3
[0059] The zinc-manganese salt solution of Example 3 includes zinc sulfate with a final concentration of 1.5 mol / L and manganese sulfate with a final concentration of 0.15 mol / L. The aqueous electrolyte includes zinc sulfate with a final concentration of 3 mol / L and manganese sulfate with a final concentration of 0.4 mol / L, and the pH of the aqueous electrolyte is 4. The pH of water is adjusted to 4 by sulfuric acid. Sulfonated enzymatic lignin is prepared by a sulfonation modification method of enzymatic lignin grafted with sulfonate.
[0060] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Example 3
[0061] Add 2g of gelatin and 0.2g of sulfonated enzymatic lignin to 10g of water, heat and stir at 70°C for 1 hour until the gelatin and sulfonated enzymatic lignin are completely dissolved to obtain a gelatin / sulfonated lignin aqueous solution, then add 10g of zinc manganese salt solution, heat and stir at 70°C for 0.5 hour to mix evenly to obtain a mixed solution, let the mixed solution stand at 4°C for 8 hours to obtain a sulfonated lignin composite gelatin hydrogel, soak the sulfonated lignin composite gelatin hydrogel in 70g of aqueous electrolyte for 72 hours to obtain a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0062] The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and the positive electrode sheet and the zinc negative electrode are assembled into a battery shell to obtain an aqueous zinc ion battery.
[0063] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0064] 2g of gelatin was added to 10g of water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then the zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain a gelatin hydrogel, and finally immersed in 70g of an aqueous electrolyte for 72 hours to obtain a reference gel electrolyte. The assembly process of an aqueous zinc ion battery using a reference gel electrolyte is the same as above.
[0065] 3. Electrochemical performance test
[0066] The aqueous zinc ion batteries using the gel electrolyte of Example 3 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0067] 4. Results Analysis
[0068] Depend on Figure 3 (a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 3 is significantly higher than the specific capacity of the aqueous zinc ion battery using the reference gel electrolyte; Figure 3(b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the discharge specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 3 is higher than that of the aqueous zinc ion battery using the reference gel electrolyte, which indicates that the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Example 3 is significantly reduced compared to the specific capacity loss of the aqueous zinc ion battery using the reference gel electrolyte. This is mainly because compared with the reference gel electrolyte, the gel electrolyte of Example 3 has a stronger ability to inhibit the formation and growth of zinc dendrites, and reduces the side reaction between the gel electrolyte and the zinc negative electrode, thereby effectively slowing down the corrosion of the gel electrolyte to the zinc negative electrode, thereby reducing the specific capacity loss of the aqueous zinc ion battery, and significantly improving the rate performance and cycle performance of the aqueous zinc ion battery.
[0069] Example 4
[0070] The zinc-manganese salt solution of Example 4 includes zinc nitrate and manganese nitrate at a final concentration of 1.5 mol / L. The aqueous electrolyte includes zinc nitrate and manganese nitrate at a final concentration of 3 mol / L, and the pH of the aqueous electrolyte is 4. The pH of the water is adjusted to 4 by sulfuric acid. Sulfonated enzymatic lignin is prepared by a sulfonation modification method of enzymatic lignin and sulfonate grafting.
[0071] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Example 4
[0072] Add 2g of gelatin and 0.2g of sulfonated enzymatic lignin to 10g of water, heat and stir at 70°C for 1 hour until the gelatin and sulfonated enzymatic lignin are completely dissolved to obtain a gelatin / sulfonated lignin aqueous solution, then add 10g of zinc manganese salt solution, heat and stir at 70°C for 0.5 hour to mix evenly to obtain a mixed solution, and then let it stand at 4°C for 8 hours to obtain a sulfonated lignin composite gelatin hydrogel, soak the sulfonated lignin composite gelatin hydrogel in 70g of aqueous electrolyte for 72 hours to obtain a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0073] The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and the positive electrode sheet and the zinc negative electrode are assembled into a battery shell to obtain an aqueous zinc ion battery.
[0074] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0075] 2g of gelatin was added to 10g of water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then 10g of zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain reference gel electrolyte. The assembly process of aqueous zinc ion battery using reference gel electrolyte is the same as above.
[0076] 3. Electrochemical performance test
[0077] The aqueous zinc ion batteries using the gel electrolyte of Example 4 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0078] 4. Results Analysis
[0079] Depend on Figure 4 (a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 4 is significantly higher than the specific capacity of the aqueous zinc ion battery using the reference gel electrolyte; Figure 4 (b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the discharge specific capacity of the aqueous zinc ion battery using the gel electrolyte of Example 4 is higher than that of the aqueous zinc ion battery using the reference gel electrolyte, which indicates that the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Example 4 is significantly reduced compared to the specific capacity loss of the aqueous zinc ion battery using the reference gel electrolyte. This is mainly because compared with the reference gel electrolyte, the gel electrolyte of Example 4 has a stronger ability to inhibit the formation and growth of zinc dendrites, and reduces the side reaction between the gel electrolyte and the zinc negative electrode, thereby effectively slowing down the corrosion of the gel electrolyte to the zinc negative electrode, thereby reducing the specific capacity loss of the aqueous zinc ion battery, and significantly improving the rate performance and cycle performance of the aqueous zinc ion battery.
[0080] Comparative Example 1
[0081] The zinc-manganese salt solution of comparative example 1 includes zinc sulfate, zinc nitrate, manganese sulfate, and manganese nitrate at a final concentration of 0.75 mol / L at a final concentration of 0.75 mol / L. The aqueous electrolyte includes zinc sulfate, zinc nitrate, manganese sulfate, and manganese nitrate at a final concentration of 1.5 mol / L at a final concentration of 1.5 mol / L, and the pH of the aqueous electrolyte is 4. The pH of the water is adjusted to 4 by sulfuric acid. Sulfonated enzymatic lignin is prepared by a method for grafting sulfonation modification of enzymatic lignin and sulfonate. Sulfonated alkali lignin is prepared by a method for grafting sulfonation modification of alkali lignin and sulfonate.
[0082] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Comparative Example 1
[0083] 2g gelatin, 0.001g sulfonated alkali lignin and 0.001g sulfonated enzymatic lignin are added to 10g water, heated and stirred at 70°C for 1 hour until gelatin, sulfonated alkali lignin and sulfonated enzymatic lignin are completely dissolved, and then 10g zinc manganese salt solution is added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain sulfonated lignin composite gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain sulfonated lignin / gelatin composite hydrogel electrolyte. The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and assembled into the battery shell with the positive electrode sheet and the zinc negative electrode to obtain an aqueous zinc ion battery.
[0084] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0085] 2g gelatin was added to 10g water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then 10g zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain gelatin hydrogel, and finally immersed in 70g aqueous electrolyte for 72 hours to obtain reference gel electrolyte. The assembly process of aqueous zinc ion battery using reference gel electrolyte is the same as above.
[0086] 3. Electrochemical performance test
[0087] The aqueous zinc ion batteries using the gel electrolyte of Comparative Example 1 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0088] 4. Results Analysis
[0089] Depend on Figure 5(a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 1 is almost the same as that of the aqueous zinc ion battery using the reference gel electrolyte; Figure 5 (b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the discharge specific capacity of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 1 is still higher than that of the aqueous zinc ion battery using the reference gel electrolyte, but the initial capacity decays very quickly. This is mainly because the mass of the sulfonated lignin in the gel electrolyte of Comparative Example 1 is less than 0.5% of the mass of gelatin compared with the reference gel electrolyte, and the ability of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 1 to inhibit the formation and growth of zinc dendrites may decrease, and the corrosion of the gel electrolyte to the zinc negative electrode may be enhanced, resulting in an increase in the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 1, which indicates that a lower lignin content will have a smaller improvement in the rate performance and cycle performance of the aqueous zinc ion battery.
[0090] Comparative Example 2
[0091] The zinc-manganese salt solution of Comparative Example 2 includes zinc sulfate, zinc nitrate, manganese sulfate, and manganese nitrate at a final concentration of 0.75 mol / L at a final concentration of 0.75 mol / L. The aqueous electrolyte includes zinc sulfate, zinc nitrate, manganese sulfate, and manganese nitrate at a final concentration of 1.5 mol / L at a final concentration of 1.5 mol / L, and the pH of the aqueous electrolyte is 4. The pH of the water is adjusted to 4 by sulfuric acid. Sulfonated enzymatic lignin is prepared by a method for grafting sulfonation modification of enzymatic lignin and sulfonate. Sulfonated alkali lignin is prepared by a method for grafting sulfonation modification of alkali lignin and sulfonate.
[0092] 1. Preparation of sulfonated lignin / gelatin composite hydrogel electrolyte and assembly of aqueous zinc ion battery of Comparative Example 2
[0093] First, 2g gelatin, 0.5g sulfonated alkali lignin and 0.5g sulfonated enzymatic lignin were added to 10g water, heated and stirred at 70°C for 1 hour until the gelatin, sulfonated alkali lignin and sulfonated enzymatic lignin were completely dissolved, then 10g zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain a sulfonated lignin composite gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain a sulfonated lignin / gelatin composite hydrogel electrolyte.
[0094] The sulfonated lignin / gelatin composite hydrogel electrolyte is added between the positive and negative electrodes, and the positive electrode sheet and the zinc negative electrode are assembled into a battery shell to obtain an aqueous zinc ion battery.
[0095] 2. Configuration of reference gel electrolyte and aqueous zinc ion assembly
[0096] 2g of gelatin was added to 10g of water, heated and stirred at 70°C for 1 hour until the gelatin was completely dissolved, and then 10g of zinc manganese salt solution was added, heated and stirred at 70°C for 0.5 hour to mix evenly, and then allowed to stand at 4°C for 8 hours to obtain gelatin hydrogel, and finally immersed in 70g of aqueous electrolyte for 72 hours to obtain reference gel electrolyte. The assembly process of aqueous zinc ion battery using reference gel electrolyte is the same as above.
[0097] 3. Electrochemical performance test
[0098] The aqueous zinc ion batteries using the gel electrolyte of Comparative Example 2 and the reference gel electrolyte were subjected to rate charge and discharge and constant current charge and discharge tests, respectively. The rates were set to 0.1 A / g, 0.3 A / g, 0.5 A / g, 1 A / g, and 2 A / g, and the constant current density was set to 1.5 A / g.
[0099] 4. Results Analysis
[0100] Depend on Figure 6 (a) It can be seen that at current densities of 0.1A / g, 0.3A / g, 0.5A / g, 1A / g, and 2A / g, the specific capacity of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 2 is slightly lower than the specific capacity of the aqueous zinc ion battery using the reference gel electrolyte; Figure 6 (b) It can be seen that after 3000 constant current charge and discharge cycles at a current density of 1.5 A / g, the specific capacity loss of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 2 is significantly greater than that of the aqueous zinc ion battery using the reference gel electrolyte. This is mainly because the mass of sulfonated lignin in the gel electrolyte of Comparative Example 2 is greater than 30% of the mass of gelatin compared to the reference gel electrolyte. The ability of the aqueous zinc ion battery using the gel electrolyte of Comparative Example 2 to inhibit the formation and growth of zinc dendrites may decrease, and the corrosion of the gel electrolyte to the zinc negative electrode may be enhanced, resulting in an increase in the specific capacity loss of the aqueous zinc ion battery using this gel electrolyte, which indicates that a high content of lignin will lead to poor rate performance and cycle performance of the aqueous zinc ion battery.
Claims
1. A sulfonated lignin / gelatin composite hydrogel electrolyte, characterized in that: The invention comprises a sulfonated lignin composite gelatin hydrogel and an aqueous electrolyte. The sulfonated lignin composite gelatin hydrogel is prepared by uniformly mixing gelatin, water, a zinc-manganese salt solution and sulfonated lignin.
2. The sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 1, characterized in that: The mass ratio of the sulfonated lignin to gelatin is 1:3 to 1:200; the mass ratio of gelatin to water is 1:2 to 1:10; the mass ratio of gelatin to zinc-manganese salt solution is 1:2 to 1:10; and the pH of the water is 2 to 6.
3. The sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 1, characterized in that: The sulfonated lignin includes lignin sulfonate, a byproduct of sulfite pulping, or one or more modified products of alkali lignin, enzymatic lignin, organic solvent lignin, steam explosion lignin prepared by graft sulfonation, sulfomethylation, and sulfite sulfonation.
4. The sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 1, characterized in that: The zinc-manganese salt solution comprises zinc salt and manganese salt, wherein the zinc salt comprises one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc bromide, zinc acetate and zinc trifluoromethanesulfonate; the manganese salt comprises one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate and manganese trifluoromethanesulfonate; the final concentration of the zinc salt in the zinc-manganese salt solution is 0.3-1.5 mol / L, and the final concentration of the manganese salt is 0.01-0.2 mol / L.
5. The sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 1, characterized in that: The mass ratio of the sulfonated lignin composite gelatin hydrogel to the aqueous electrolyte is 1:2 to 1:5; the aqueous electrolyte is prepared by dissolving and mixing water-soluble zinc salts and water-soluble manganese salts, wherein the water-soluble zinc salts include one or more of zinc sulfate, zinc nitrate, zinc chloride, zinc bromide, zinc acetate, and zinc trifluoromethanesulfonate; the water-soluble manganese salts include one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide, manganese acetate, and manganese trifluoromethanesulfonate; the final concentration of the water-soluble zinc salt in the aqueous electrolyte is 1.5 to 3 mol / L, and the final concentration of the water-soluble manganese salt is 0.1 to 0.4 mol / L. The pH of the aqueous electrolyte is 3.5 to 7.
6. A method for preparing the sulfonated lignin / gelatin composite hydrogel electrolyte as claimed in claim 1, characterized in that: The following steps are involved: 1) adding gelatin and sulfonated lignin into water, heating and stirring to form a gelatin / sulfonated lignin aqueous solution, adding a zinc manganese salt solution into the gelatin / sulfonated lignin aqueous solution, stirring to obtain a mixed solution, and allowing the mixed solution to stand at low temperature to obtain a sulfonated lignin composite gelatin hydrogel; 2) Soaking the sulfonated lignin composite gelatin hydrogel in an aqueous electrolyte to obtain a hydrogel.
7. The method for preparing the sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 6, characterized in that: The heating temperature in step 1) is 60-80°C; the low temperature is 0-10°C.
8. The method for preparing the sulfonated lignin / gelatin composite hydrogel electrolyte according to claim 6, characterized in that: The soaking time in step 2) is 2 to 6 days.
9. An aqueous zinc ion battery, characterized in that: The invention comprises the sulfonated lignin / gelatin composite hydrogel electrolyte as described in any one of claims 1 to 5.